Dual-cycle immobilization to reuse both enzyme and support by reblossoming enzyme–inorganic hybrid nanoflowers. Issue 29 (30th April 2018) - Yu, Jianyun; Wang, Chenhui; Wang, Anming; Li, Ningning; Chen, Xinxin; Pei, Xiaolin; Zhang, Pengfei; Wu, Stephen Gang
Abstract : Both enzyme and support can be recycled using dual-cycle immobilization method by reblossoming the enzyme–inorganic hybrid nanoflowers. Abstract : To achieve dual-reuse of both enzyme and support in enzyme immobilization, hybrid nanoflowers (hNFs) were synthesized and crystallized in aqueous solution using calcium phosphate as inorganic component and enzyme as organic component. When hNFs lost their catalytic activity after reuse for times, they underwent dissolution and recrystallization to achieve the dual-cycle of enzyme and support. Six enzymes including papain, bromelain, trypsin, Lipase from Porcine Pancreas (PPL), Lipase from Thermomyces lanuginosus (TLL) and Lipase B from Candida antarctica (CALB) were chose as model enzymes and the obtained hNFs all presented high catalytic activity and thermal stability. The highest catalytic efficiency ( K cat / K m ) of TLL-hNFs was 38.52 mM −1 s −1, 21.7 folds than that of free enzyme. Moreover, after heating for 6 h at 70 °C, the residual activities of TLL-hNFs, PPL-hNFs, and CALB-hNFs, were 78.3%, 72.9% and 84.3%, which were 4.57, 2.61 2.35 folds of that of their corresponding free one. Furthermore, the recovery rate of Ca3 (PO4 )2 were above 95% by recrystallizing the calcium phosphate with fresh enzymes after dissolving the used hNFs and removing the denatured enzyme. The recrystallized hNFs using the recovered phosphate salts and fresh enzymes all gave the consistent catalytic activities. This sustainable dual-cycle method depending on calcium phosphate crystallization, dissolution and recrystallization, was facile and efficient and can also be applied to other enzymes immobilization for industrial biocatalysis.